Glomerular IgA Deposition and Serum Antineutrophil Cytoplasmic Antibody Positivity in a Child With Dystrophic Epidermolysis Bullosa: Case Report and Literature Review - Yu, Ling; Huang, Guoping; Lu, Zhihong; Wang, Jingjing; Gu, Weizhong; Li, Junping; Mao, Jianhua (Frontiers in Pediatrics, 2022)
Patients with epidermolysis bullosa (EB) could develop significant urological complications, such as hydroureteronephrosis, renal amyloidosis and IgA nephropathy (IgAN). Here, we presented a 12-year-old boy carrying pathogenic COL7A1 mutation with diagnosis of dystrophic epidermolysis bullosa (DEB). The patient had concomitant gross hematuria and proteinuria. Pathological examinations and immunostaining of renal biopsy showed glomeruli with mesangial hypercellularity and deposition of IgA, which were indicative of IgAN. Interestingly, serological evaluation showed antineutrophil cytoplasmic antibody (ANCA) directed against myeloperoxidase and proteinase 3. Treatment with glucocorticoid, immunosuppressants, angiotensin-converting enzyme inhibitor and antibiotics efficiently improved hemato-proteinuria, and ANCAs became negative as well. This case of DEB presented a unique collection of clinical manifestations and pathological alterations. IgAN and serum positive ANCA were possibly associated with sustained infection secondary to DEB, and can be managed by empirical treatment for primary IgAN.